Reuse of mining tailing as raw crude for the elaboration of aggregates of construction for the making of bricks and tile - Romero Baylón, Alfonso (2010)
The present paper treats about the reuse of the tailing through the shape of an aggregate of construction for the making of bricks ans aggregates of construction. Actually, there is a huge tailing pond in Ticapampa which belongs to the Mining Company Alianza, which has been built near the shore of the Santa river in km 170 and it is parallel to the highway Pativilca-Huaraz, which has a dimension of 750 X 200 meters and it has 19 metres high, which constitute an environment mining passive of high proportions by the huge volume that hás been located near to the área of the Santa River Basin. In that sense, there is a need of formulating solutions for this sort of environment problem which is a national concern and that was the main reason for developing many projects of research at The Ticapampa zone, in charge of a group of researchers from La Universidad Nacional Mayor de San Marcos, who proposed give an added value to this tailing through the reuse of the tailing under the shape of na aggregate of construction which constitute the raw crude for the elaboration of aggregates of construction.